2017
DOI: 10.1039/c7cp04476c
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of excited state proton transfer in nitro substituted 10-hydroxybenzo[h]quinolines

Abstract: The ground state tautomerism and excited state intramolecular proton transfer (ESIPT) of 10-hydroxybenzo[h]quinoline (HBQ) and its nitro derivatives, 7-nitrobenzo[h]quinolin-10-ol (2) and 7,9-dinitrobenzo[h]quinolin-10-ol (3), have been studied in acetonitrile using steady state as well as time dependent spectroscopy and quantum-chemical calculations. In addition to the enol form absorbance in the range 360-390 nm, the absorption spectra of 2 and 3 exhibit a red shifted band at ∼450 nm. Chemometric data proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…The M06-2× functional was selected by a benchmarking procedure, which has shown that there is good empirical relations between the relative stability of the tautomers, defined as ΔE, and the experimentally determined ΔG o values of set of tautomeric dyes in cycloxexane [52,53]. This qualitative approach shows very good results in predicting the position of tautomeric equilibria for compounds with intramolecular hydrogen bonds as well as describing ground and excited state proton transfer mechanisms [54][55][56][57][58]. Although the computationally ΔG o values should be preferable, their accuracy is under question even at high level calculations for compounds of the size used in the current study [59,60].…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%
“…The M06-2× functional was selected by a benchmarking procedure, which has shown that there is good empirical relations between the relative stability of the tautomers, defined as ΔE, and the experimentally determined ΔG o values of set of tautomeric dyes in cycloxexane [52,53]. This qualitative approach shows very good results in predicting the position of tautomeric equilibria for compounds with intramolecular hydrogen bonds as well as describing ground and excited state proton transfer mechanisms [54][55][56][57][58]. Although the computationally ΔG o values should be preferable, their accuracy is under question even at high level calculations for compounds of the size used in the current study [59,60].…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%
“…The M06-2X functional was selected for three reasons. First, it has shown that there is good empirical relations between the relative stability of the tautomers, defined as ΔE, and the experimentally determined ΔG o values of tautomeric azo and azomethyne dyes in cyclohexane and acetonitrile [ 50 , 58 , 59 ], and of heterocyclic tautomers [ 49 , 53 ]. Second, the use of M06-2X provides very good predictability of the E/Z isomerization ratio in some rotary switches [ 51 , 60 ].…”
Section: Theoretical Simulationsmentioning
confidence: 99%
“…The theoretical design of such proton transfer-based systems faces many challenges related to correct prediction of the ground state tautomerism, solvent effects and excited state dynamics upon irradiation. Recently, we have been able to accumulate knowledge about using density functional theory (DFT) calculations for correct prediction of the ground and excited state tautomerism of dyes and heterocycles [ 49 , 50 , 51 , 52 , 53 ], which gives a good opportunity to attempt the design of proton cranes. 8-(Pyridin-2-yl)quinolin-7-ol, where 7-hydroxy quinoline ( 4 ) serves as a tautomeric sub-unit, has been selected as a platform to investigate the effect of the substituents in the pyridine crane sub-unit ( Scheme 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the substituent effect on proton transfer process has aroused great interest of many researchers [59][60][61][62][63]. A large number studies showed that ESPT dynamics was closely correlated with the substituent properties and substituted positions.…”
Section: Introductionmentioning
confidence: 99%